Characteristics of Drug Therapy in Hemorrhoid Patients at Ibnu Sina Hospital, Makassar - Feri Ramadan; Berry Erida Hasbi; Suci Noviyanah Anshary; Azis Beru Gani; Abdul Mubdi Ardiansar Arifuddin Karim (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2025)
Hemorrhoids are a common anorectal disorder, with management depending on severity and clinical features. This study aimed to describe the characteristics of pharmacological therapy in hemorrhoid patients at Ibnu Sina Hospital, Makassar. A descriptive cross-sectional study was conducted on 43 patients from January to December 2024 using total sampling. Data were collected through interviews and medical records, then analyzed descriptively. Most patients were aged 36–45 years (27.9%) and male (58.1%). Conservative management was predominant, while surgery was performed in advanced cases. The most common single therapy was oral anti-hemorrhoids (9.3%), while the most frequent combination was anti-hemorrhoids plus analgesics (16.3%). Active substances included diosmin–hesperidin (60.5%) as anti-hemorrhoids, ibuprofen and ketorolac (18.6% each) as analgesics, ceftriaxone and cefuroxime (9.3%) as antibiotics, lactulose (18.6%) as laxatives, and tranexamic acid (46.5%) as antifibrinolytic. In conclusion, hemorrhoids were more common in middle-aged males. Conservative management remained the main approach, with diosmin–hesperidin as the most widely used pharmacological therapy. Keywords: Hemorrhoid, pharmacological therapy, conservative